Law Student Wellbeing: Benefits of Promoting Psychological Literacy and Self-Awarness Using Mindfulness, Strengths Theory and Emotional Intelligence - Colin James (Legal Education Review)
The higher education experience is a significant financial, socio-cultural and emotional challenge for an ever more diverse cohort of students. Nowhere is this more pronounced than in the law school where a growing number of studies reveal a disproportionate level of psychological distress and depression amongst students. One means of addressing this issue lies in providing social and emotional support to students through effective curricular pastoral care – yet addressing psychological distress and mental illness requires an institutional commitment which will only develop where there is sufficient interest amongst at least some institutional members. To generate interest though requires a justification for adopting this approach within the role of the legal academic. This paper makes the connection between effective embedded pastoral care in the law school and student wellbeing. It then explores the philosophy and practice of four academics working together in an integrated first year LLB program to explain the foundation of their approach to student support. Finally, it identifies how a more empathetic approach might be justified in the law school